2022
DOI: 10.1097/jcma.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pneumothorax and pulmonary hemorrhage following computed tomography-guided transthoracic core-needle biopsy of subpleural lung lesions

Abstract: Background: Identifying the risk factors for complications may alert the physicians and help them adjust their plans before performing computed tomography-guided lung biopsies. Reportedly, a pleura-nodule distance longer than 2.0 cm is a strong predictor for pneumothorax and pulmonary hemorrhage. However, the rate and risk factors of biopsy-associated complications in subpleural lesions have not been assessed. This study aimed to identify the risk factors for pneumothorax and pulmonary hemorrhage in subpleural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, needle depth to the lesion longer than 2.0 cm is a strong predictor for pulmonary hemorrhage. For subpleural lesions ≤2.0 cm in depth, a higher needle-pleura angle may reduce the risk of pulmonary hemorrhage [ 4 ]. Interestingly, An et al [ 5 ] reported that post-biopsy hemorrhage may be a protective factor for pneumothorax.…”
Section: Introductionmentioning
confidence: 99%
“…For example, needle depth to the lesion longer than 2.0 cm is a strong predictor for pulmonary hemorrhage. For subpleural lesions ≤2.0 cm in depth, a higher needle-pleura angle may reduce the risk of pulmonary hemorrhage [ 4 ]. Interestingly, An et al [ 5 ] reported that post-biopsy hemorrhage may be a protective factor for pneumothorax.…”
Section: Introductionmentioning
confidence: 99%